2016
DOI: 10.1021/acs.jmedchem.6b00753
|View full text |Cite
|
Sign up to set email alerts
|

Fulvestrant-3 Boronic Acid (ZB716): An Orally Bioavailable Selective Estrogen Receptor Downregulator (SERD)

Abstract: Orally bioavailable SERDs may offer greater systemic drug exposure, improved clinical efficacy, and more durable treatment outcome for patients with ER-positive endocrine-resistant breast cancer. We report the design and synthesis of a boronic acid modified fulvestrant (5, ZB716), which binds to ERα competitively (IC50 = 4.1 nM) and effectively downregulates ERα in both tamoxifen-sensitive and tamoxifen-resistant breast cancer cells. Furthermore, It has superior oral bioavailability (AUC = 2547.1 ng·h/mL) in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 35 publications
5
81
0
Order By: Relevance
“…While effective, each is not fully optimal, and some troubling side effects that may limit their clinical utility have been noted (8). RAD-0910 (40,41) and boronic acid derivatives of Fulvestrant and GW7604 (42,43) show promise, but clinical evaluations are at very early stages. Thus, there is an unmet need for orally active antiestrogens with an improved clinical profile and reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…While effective, each is not fully optimal, and some troubling side effects that may limit their clinical utility have been noted (8). RAD-0910 (40,41) and boronic acid derivatives of Fulvestrant and GW7604 (42,43) show promise, but clinical evaluations are at very early stages. Thus, there is an unmet need for orally active antiestrogens with an improved clinical profile and reduced side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Its structure is liable to metabolism at C3 and C17 of its steroidal nucleus resulting in rapid deactivation. Chemical modification at C3 by addition of boronic acid yielded the new compound ZB716 with improved metabolic stability (Figure ) . Compounds containing an acetate group are liable to metabolism through de‐acetylation.…”
Section: Effect Of Chemical Structure On Physicochemical Properties Amentioning
confidence: 99%
“…Metabolic stability can be enhanced by alteration of the chemical structure. Example of this is blocking the metabolism liable site and chemical derivatization of small molecules. The substitution of l ‐amino acids by d ‐amino acids and the N ‐methylation in amino acids and peptides can be done to improve stability of peptide‐based therapeutics …”
Section: Chemical and Pharmaceutical Solutionsmentioning
confidence: 99%
“…11,12) Boronic acids and esters emerged recently as biocompatible bioisosters and prodrugs of phenolic alcohols with enhanced bioavailability and selectivity. [13][14][15][16] Jiang et al showed that boronic derivatives of tamoxifen, the first line therapy in estrogen receptor positive (ER+) breast cancer, inhibit the growth of (ER+) breast cancer cell lines with potencies comparable to or greater than that of the parent drug, 4-hydroxytamoxifen. Moreover, those analogues were taken up by cancerous cells up to 4 times more efficiently than the parent phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, those analogues were taken up by cancerous cells up to 4 times more efficiently than the parent phenol. 13) The aim of this work is to develop boronic derivatives of phenanthroindolizidine alkaloids and to evaluate their antiproliferative activity in-vitro. (R)-6-O-Desmethylantofine (1) was chosen as it is characterized by high cytotoxic activity and it possesses an amenable phenol functional group.…”
Section: Introductionmentioning
confidence: 99%